2017
DOI: 10.1016/j.rgmx.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo asociados a recaída de enfermedad por reflujo gastroesofágico en pacientes de primer nivel de atención exitosamente tratados con inhibidor de la bomba de protones

Abstract: The relapse rate after short-term treatment with omeprazole was high. The consumption of citrus fruits and NSAIDs increased the possibility of GERD relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There was a negative association between coffee and GERD symptoms [ 23 , 24 ], while in another study, there was a role of coffee in increasing the GERD symptoms [ 29 ]. However, the coffee consumption is a risk factor for GERD relapsing after treatment with PPIs [ 30 ]. Giving the fact that many soft drinks are highly acidic, a change in the intra-esophageal PH may precipitate a GERD-like symptom, which may also increase the acid load in the stomach leading to increased probability of gastroesophageal reflux [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a negative association between coffee and GERD symptoms [ 23 , 24 ], while in another study, there was a role of coffee in increasing the GERD symptoms [ 29 ]. However, the coffee consumption is a risk factor for GERD relapsing after treatment with PPIs [ 30 ]. Giving the fact that many soft drinks are highly acidic, a change in the intra-esophageal PH may precipitate a GERD-like symptom, which may also increase the acid load in the stomach leading to increased probability of gastroesophageal reflux [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…[19] Previous studies have indicated that the risk factors of GORD include sleep apnea, unhealthy diet, obesity, psychological factors, current smoking, causes of heart disease, drinking and diabetes. [20][21][22] However, GORD can be prevented, and changing the above risk factors through education can be an important prevention strategy for GORD. Although the guidelines recommend patient education, there are few previous studies on GORD patient education, and the results are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical power calculation was carried out to estimate the sample size for the superiority trial. According to our review of studies, relapse rates of patients with healed lesions have been reported to be 54% to 66.2% at 12 wk after drug therapy was withdrawn[2,20,21], so our estimation of the average relapse rate for the placebo group was 60%. Also, cured RE patients who received an additional maintenance treatment had a relapse rate of 10% at 12 wk and 28.4% to 30% at 32 wk after drug therapy was stopped[1,22].…”
Section: Methodsmentioning
confidence: 99%
“…Frequent relapses are common with RE, resulting in significant physical pain and financial burden on patients. Studies on the treatment of RE are scarce[1,2]. The first-line treatment for RE is administration of proton pump inhibitors (PPIs)[3], which are the most commonly prescribed drugs worldwide.…”
Section: Introductionmentioning
confidence: 99%